Gender Differences in the Associations Between Physical Activity, Smartphone Use, and Weight Stigma - Xu, Ping; Chen, Jung-Sheng; Chang, Yen-Ling; Wang, Xiaodong; Jiang, Xingyong; Griffiths, Mark D.; Pakpour, Amir H.; Lin, Chung-Ying (Frontiers in Public Health, 2022)
Background Physical activity (PA) is important for health. However, there is little evidence on how weight stigma, time spent on sedentary activities (including smartphone, social media, online learning), time spent on outdoor activity, and nomophobia associate with PA among Chinese individuals with consideration of gender. The present study examined the aforementioned associations in the COVID-19 pandemic era. Methods University students (N = 3,135; 1,798 females, 1,337 males) with a mean age of 19.65 years (SD = 2.38) years completed an online survey from November to December, 2021. The online survey assessed weight stigma (using the Perceived Weight Stigma Scale and Weight Bias Internalization Scale), PA (using the International Physical Activity Questionnaire Short Form), time spent on different activities (using self-designed items for time on smartphone, outdoor activity, social media, and online learning), and nomophobia (using the Nomophobia Questionnaire). Parallel mediation models were constructed (dependent variable: PA; mediators: perceived weight stigma, weight-related self-stigma, time spent on smartphone, time spent on outdoor activity, time spent on social media, and time spent online learning; independent variable: nomophobia) and evaluated using Hayes' Process Macro Model 4 (IBM SPSS 20.0). Results Weight-related self-stigma (β = −0.06; p = 0.03), time spent on outdoor activity (β = 0.21; p < 0.001), time spent on social media (β = 0.07; p = 0.02), time spent on online learning (β = 0.06; p = 0.03), and nomophobia (β = −0.07; p = 0.01) were all significant factors explaining the PA among female participants. Perceived weight stigma (β = −0.07; p = 0.01), time spent on outdoor activity (β = 0.27; p < 0.001), and time spent on online learning (β = 0.10; p = 0.002) were all significant factors explaining PA among male participants. Conclusion Chinese healthcare providers should design programs on weight stigma reduction and outdoor activity improvement to enhance PA among university students.